Description of Paracymbiomma gen. nov., a new genus of prodidomid spiders from the Neotropical region (Araneae: Prodidomidae) including a new troglobite species - Rodrigues, Bruno V. B.; Cizauskas, Igor; Rheims, Cristina A. (Zootaxa, 2018)
Paracymbiomma gen. nov. is proposed to include six new species from Brazil: P. angelim sp. nov. (♂ ♀) from São Paulo, P. carajas sp. nov. (♂ ♀), P. bocaina sp. nov. (♂ ♀) and P. caecus sp. nov. (♂ ♀) from Pará, P. doisirmaos sp. nov. (♂) from Pernambuco and P. pauferrense sp. nov. (♂) from Paraíba. The genus is included in Theuminae by having the sternum with posterior region without rebordered margins, strongly protruding between coxae IV and with numerous long and erect setae, and by the vulva with highly convoluted ducts. It can be distinguished from the other members of the subfamily by the male palp with paracymbium, single RTA, bulb with sclerotized conductor and partly sclerotized median apophysis, and by the female epigyne with posteromedian atrium and sclerotized margin, and vulva with copulatory ducts long, strongly convoluted laterally with proximal part (closest to copulatory openings) translucent. Paracymbiomma carajas sp. nov., P. bocaina sp. nov. and P. caecus sp. nov. occur exclusively in ferruginous caves. We provide a discussion on specializations and adaptations of Paracymbiomma gen. nov. and other species of Prodidomidae to the subterranean environment.